2021
DOI: 10.52398/gjsd.2021.v1.i1.pp50-66
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Intelligence (CQ) and Cultural Exposure Through Mobility Programs

Abstract: As a result of globalisation, a significant proportion of companies operate across borders and in many cases, work communities are also organised from workers with diverse cultural backgrounds. Due to the intensive flow of services, goods and labour, and cultural differences, conflicts can arise, and these tensions can negatively affect people and organisations' well-being and performance. Nowadays, cultural knowledge and intercultural competencies are more appreciated and highly requested by most employers.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…CI has been examined as both an antecedent and consequent of studying abroad, and in this study, we examined it as an antecedent of the intention to study abroad. In line with previous studies, we found CI to be associated with openness facets (Ang et al, 2006;Depaula et al, 2016;G€ okten and Emil, 2019;Li et al, 2016;Shu et al, 2017) and with studying abroad (Anh et al, 2021;Luchkiw, 2013;Pasztor, 2021). Students who score higher on CI are more open to experience and more likely to study abroad.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…CI has been examined as both an antecedent and consequent of studying abroad, and in this study, we examined it as an antecedent of the intention to study abroad. In line with previous studies, we found CI to be associated with openness facets (Ang et al, 2006;Depaula et al, 2016;G€ okten and Emil, 2019;Li et al, 2016;Shu et al, 2017) and with studying abroad (Anh et al, 2021;Luchkiw, 2013;Pasztor, 2021). Students who score higher on CI are more open to experience and more likely to study abroad.…”
Section: Discussionsupporting
confidence: 91%
“…, 2017) and with studying abroad (Anh et al. , 2021; Luchkiw, 2013; Pasztor, 2021). Students who score higher on CI are more open to experience and more likely to study abroad.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pandemic was also a warning signal to have students prepared with Information and Communication Technologies (ICT) and collaborative skills and educate them to remain interested in life-long learning (Hirschi, 2017). This technological-digital shift affects profoundly not only education but future employees and business structures as well: knowledge and talent replace raw materials and capital and become the most competitive assets (Bartram, 2005;Pásztor, 2021). Implementing strategic workforce planning and talent management can give each organization a more agile approach and a new dynamic for progress and development (de Lucas-Ancillo, del Val-Núñez & Gavrila, 2020).…”
Section: Education 40mentioning
confidence: 99%